Docosahexaenoic acid is a beneficial replacement treatment for spinocerebellar ataxia 38. Issue 4 (22nd October 2017) - Manes, Marta; Alberici, Antonella; Di Gregorio, Eleonora; Boccone, Loredana; Premi, Enrico; Mitro, Nico; Pasolini, Maria Pia; Pani, Claudia; Paghera, Barbara; Perani, Daniela; Orsi, Laura; Costanzi, Chiara; et al.
Abstract : Objective: Spinocerebellar ataxia 38 (SCA38) is caused by mutations in the ELOVL5 gene, which encodes an elongase involved in the synthesis of polyunsaturated fatty acids, including docosahexaenoic acid (DHA). As a consequence, DHA is significantly reduced in the serum of SCA38 subjects. In the present study, we evaluated the safety of DHA supplementation, its efficacy for clinical symptoms, and changes of brain functional imaging in SCA38 patients. Methods: We enrolled 10 SCA38 patients, and carried out a double‐blind randomized placebo‐controlled study for 16 weeks, followed by an open‐label study with overall 40‐week DHA treatment. At baseline and at follow‐up visit, patients underwent standardized clinical assessment, brain 18‐fluorodeoxyglucose positron emission tomography, electroneurography, and ELOVL5 expression analysis. Results: After 16 weeks, we showed a significant pre–post clinical improvement in the DHA group versus placebo, using the Scale for the Assessment and Rating of Ataxia (SARA; mean difference [MD] = +2.70, 95% confidence interval [CI] = +0.13 to + 5.27, p  = 0.042). At 40‐week treatment, clinical improvement was found significant by both SARA (MD = +2.2, 95% CI = +0.93 to + 3.46, p  = 0.008) and International Cooperative Ataxia Rating Scale (MD = +3.8, 95% CI = +1.39 to + 6.41, p  = 0.02) scores; clinical data were corroborated by significant improvement of cerebellar hypometabolism (statistical parametric mapping analyses, false discovery rate corrected). We also showed a decreased expression of ELOVL5 in patients' blood at 40 weeks as compared to baseline. No side effect was recorded. Interpretation: DHA supplementation is a safe and effective treatment for SCA38, showing an improvement of clinical symptoms and cerebellar hypometabolism. Ann Neurol 2017;82:615–621